2023
DOI: 10.1186/s40529-023-00373-0
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-anatomical, and chemical characterization of some calcareous Mediterranean red algae species

Abstract: Climatic changes are anticipated to have a detrimental effect on calcifying marine species. Calcareous red algae may be especially vulnerable to seasonal variations since they are common and essential biologically, but there is little research on the morpho-anatomical, and chemical characterization of such species. This study conducted the seasonal investigation of the three dominant Mediterranean calcified red algae. Morphological and 18S rRNA analysis confirmed the identification of collected species as Cora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 83 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…These extracts have demonstrated positive antibacterial activity against diverse strains of pathogens [ 18 , 38 ]. The variance in bioactive compounds can be attributed to factors such as the solvent type, extraction method, and the season during which the algae were collected [ 39 , 40 ]. Our own findings revealed that the methanol extract of A. platensis and the acetone extract of P. scopulorum exhibited no antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…These extracts have demonstrated positive antibacterial activity against diverse strains of pathogens [ 18 , 38 ]. The variance in bioactive compounds can be attributed to factors such as the solvent type, extraction method, and the season during which the algae were collected [ 39 , 40 ]. Our own findings revealed that the methanol extract of A. platensis and the acetone extract of P. scopulorum exhibited no antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Red algae, or Rhodophyta, are diverse eukaryotic organisms that inhabit freshwater lakes and marine environments, showcasing a distinctive red color from phycoerythrin, carotenoids, and chlorophyll a pigment [95]. Their starch and galactan sulfate polymer content positions red algae as a viable feedstock for bioplastic production [96].…”
Section: Main Compounds Of Bioplastic Produced From Red Algaementioning
confidence: 99%
“…Macroalgae and phytoplankton are predominant contributors to marine primary production [44,45]. Despite once being considered predecessors of land plants, algae lack the characteristic plant structures such as stems, leaves, and roots.…”
Section: Naturally-growing Macroalgaementioning
confidence: 99%
“…Macroalgae have a complex lifecycle displaying annual and perennial life histories, alternation of generation, as well as asexual and sexual reproduction. They are a rich source of bioactive compounds, including polysaccharides, proteins, lipids, vitamins, minerals, and secondary metabolites [45]. The composition of these bioactive compounds varies among different species, as well as based on growth factors such as environmental conditions, growth stage, and geographical location [89,90].…”
Section: Biochemical Composition Of Macroalgae and Seagrassmentioning
confidence: 99%